Book review: “The dreams behind the music: learn creative dreaming as 100+ top artists reveal their breakthrough inspirations" by Craig Sim Webb - Schredl, Michael (International journal of dream research, 2019)
The book by Craig Sim Webb includes a large variety of stories showing how dreams can provide inspirations for melodies, lyrics, song titles, instrumentation, arrangements, new performance ideas, musical instrumentation inventions, and even help to train performing skills. These accounts are backed up by his own experience being a dream expert and a singer-songwriter. The book also includes instructions to increase dream recall and how to incubate music dreams in order to harvest the dream ideas.
Gesehen am 11.10.2019
Keywords: Rezension